Frequency of Systemic Lupus Erythematosus Was Decreasing Among Hospitalized Patients From 2013 to 2017 in a National Database in China - Tan, Ying; Yu, Feng; Long, Jianyan; Gan, Lanxia; Wang, Haibo; Zhang, Luxia; Zhao, Minghui (Frontiers in Medicine, 2021)
Backgrounds Limited data was reported for the frequency of SLE in China. The aim of the present study was to investigate the frequency, geographical distribution, and ethnic distribution of SLE in hospitalized patients in China using data from the Hospital Quality Monitoring System (HQMS). Methods We investigated hospitalized patients in a national inpatient database covering 46.0% of tertiary hospitals in China from 2013 to 2017. Data regarding the diagnosis of SLE were extracted based on ICD-10 codes. Data from the front page of the inpatient records were collected and analysed, including frequency, geographic distributions and demographic characteristics of SLE. Results Among 158.3 million inpatients attended during the study period, 0.31% (491,225) were diagnosed with SLE. The frequency of SLE decreased during the study period (from 0.30% in 2013 to 0.27% in 2017). The frequency of SLE increased with latitude (0.21% in northern China and 0.39% in southern China in 2017). Hospitalizations mostly occurred in winter (31.24%). The Li population had the highest frequency of patients with SLE (0.76%). The all-cause in-hospital mortality rate of SLE decreased from0.74% (255/34,746) in 2013 to 0.54% (295/54,168) in 2017. The percentage of SLE patients with infections increased from 3.14% in 2013 to 4.72% in 2017. The percentage of SLE patients with tumours and thrombosis also increased slightly from 0.85% and 1.43% in 2013 to 1.27% and 2.45% in 2017, respectively. Conclusion Our present investigation of hospitalized patients provided epidemiological information on SLE in China for the first time. A spatial and ethnic clustering trend of SLE was observed.